EFFECTIVENESS OF Lactobacillus plantarum Mut 7 AGENTS FERMENTATION TO REDUCE TREMBESI (Albizia saman) SAPONINS CONTENT - Sariri, Ahimsa Kandi (Proceeding of International Congress, 2014)
This objectives research to assess the ability of Lactobacillus plantarum Mut 7 in reducing the saponincontent while increasing the nutrient content in the leaves, young fruit and trembesi pods (Albiziasaman). The study was conducted using a completely randomized design. The addition of Lactobacillusplantarum Mut 7 on the fermentation of 3 parts, namely plant leaves, young fruit and pods. Each treatmentwas repeated as many as four replications to obtain 12 units of the experiment. This study concludedthat the fermentation using Lactobacillus plantarum Mut 7 reduced saponin content and increase nutrientcontent, especially the content of crude protein.Keywords: fermentation, trembesi, saponin, nutrient